Implementasi Sistem Kriptografi Hybrid RSA dan DES untuk Pengamanan Data Teks - Putu Ayu Wulan Satya Dewi; I Gede Santi Astawa (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2025)
Data security is a crucial aspect in the digital age. Symmetric algorithms such as the Data Encryption Standard (DES) offer high-speed encryption, but have fundamental weaknesses in terms of secure key distribution. On the other hand, asymmetric cryptography such as RSA can overcome key distribution issues, but is computationally inefficient for encrypting large volumes of data. To address these challenges, this article demonstrates the implementation of a hybrid cryptographic system that integrates the strengths of both algorithms. This system leverages the RSA algorithm, which is based on principles of number theory such as modular arithmetic and the difficulty of prime factorization, to securely encrypt and distribute DES session keys. Subsequently, the DES algorithm is used to quickly and efficiently encrypt textual data. Through an explanation of the mathematical processes and programmed implementation, this research demonstrates that the hybrid approach can both secure and restore plaintext data intact.